Ship breaker - Bacigalupi, Paolo (New York : Little, Brown, 2010)
In a futuristic world, teenaged Nailer scavenges copper wiring from grounded oil tankers for a living, but when he finds a beached clipper ship with a girl in the wreckage, he has to decide if he should strip the ship for its wealth or rescue the girl.
A Junior Library Guild selection
Keywords: Conduct of life -- Fiction; Recycling (Waste) -- Fiction; Science fiction; Printz Medal; Young adult fiction; Science fiction -- Juvenile; Conduct of life -- Juvenile fiction; Recycling (Waste, etc.) -- Juvenile fiction